2006
DOI: 10.1111/j.1470-6431.2006.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception and attitudes on infant feeding practices and baby milk formula in East Malaysia

Abstract: A survey on infant feeding and weaning practices of 505 respondents who had children currently aged between 0 and 6 years old was carried out in Kota Kinabalu, Sabah. The decisive factors, which influence parents’ purchase decision of infant and follow‐up formula were also determined. Initiation of breastfeeding was practised by 86.3% of respondents, but only 8.3% of 436 respondents exclusively breastfed for 6 months and beyond. An association was established where parents with a higher educational level (χ 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
2
7
1
Order By: Relevance
“…When questioned on who influenced their decision to purchase functional weaning foods, family and friends were the most important influencer (positive or negative testimonials). These results were consistent with other research that found family and friends' opinions were considered as one of the top determinants of purchasing formula milk in Malaysia (Yee & Chin, 2007). As new (first-time) and inexperienced parents do not have much experience of, or information on, functional weaning food product, families and friends who had past experiences with their own children were viewed as being good sources of information as they could share their knowledge and give product reviews.…”
Section: Important Referents and Influencessupporting
confidence: 90%
See 1 more Smart Citation
“…When questioned on who influenced their decision to purchase functional weaning foods, family and friends were the most important influencer (positive or negative testimonials). These results were consistent with other research that found family and friends' opinions were considered as one of the top determinants of purchasing formula milk in Malaysia (Yee & Chin, 2007). As new (first-time) and inexperienced parents do not have much experience of, or information on, functional weaning food product, families and friends who had past experiences with their own children were viewed as being good sources of information as they could share their knowledge and give product reviews.…”
Section: Important Referents and Influencessupporting
confidence: 90%
“…Parents were found to be brand loyal or to only purchase brands that they were familiar with. These results are consistent with Yee and Chin (2007) where parents in Malaysia were found to have quite a high level of brand loyalty as 70.7% of them had no experience at all with other brands in purchasing formula milk products. This is because parents will not switch to other brands when the particular brand is suitable for their babies.…”
Section: Important Referents and Influencessupporting
confidence: 87%
“…While breastfeeding is clearly a priority for Malawi, strengthening of its legislation around the Code is needed. Marketing of BMS leads to higher rates of bottle feeding and negatively affects breastfeeding rates (Alfaleh, ; Phoutthakeo et al, ; Yee & Chin, ). Enhanced legislation and enforcement of the Code will be critical to maintaining an environment that promotes and protects breastfeeding (WHO, ).…”
Section: Discussionmentioning
confidence: 99%
“…The final sample represented a diverse group of mothers in terms of occupation, education, family structure, age and income. Several previous studies in the context of baby care products (Chen et al, 2004;Yee and Chin, 2007;Ballester and Aleman, 2001; Broadbridge and Morgan, 2001) have also used mothers as their sample. Mothers are suitable for this study as they are considered to be closest to their babies, and to spend the most amount of time with them, meaning that they make the final decisions regarding the brands selected for their babies' use.…”
Section: Sample and Data Collectionmentioning
confidence: 99%